THE DEVELOPING OF PROTOTYPE TOOL DETERMINING CELESTIAL POSITIONS (WAH 1.0) AS LEARNING MEDIA IN EARTH AND SPACE SCIENCE COURSE - Wiji Aziiz Hari Mukti; Ahmad Walid (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2018)
The purpose of this study is a media creation for the deciding tool revealed that the position of the heavenly bodies can be created and used to determine the position of the heavenly bodies so that it can be used as a learning media in the Earth and space science course. The working principle of this tool is to use the coordinates of the horizon. Tools used i.e. compass, bows, tripod, and camera. To test the accuracy of the application use Stellarium mobile version 1.25. The results of this study are to test the accuracy of the altitude angle obtained its accuracy level results 100%. Whereas, in order to test the accuracy of the altitude reached the corner of 99.86%.